The complete mitochondrial genome of Trissolcus japonicus (Hymenoptera: Scelionidae), the candidate for the biological control of Halyomorpha halys (Hemiptera: Pentatomidae). Issue 8 (3rd August 2021) - Nardi, Francesco; Cucini, Claudio; Cardaioli, Elena; Paoli, Francesco; Sabbatini Peverieri, Giuseppino; Roversi, Pio Federico; Frati, Francesco; Carapelli, Antonio
Abstract: The samurai wasp Trissolcus japonicus (Ashmead, 1904) is a parasitoid hymenopteran that came into the limelight as the natural enemy of Halyomorpha halys . Here, we present the complete sequence of the mitochondrial genome of the CREATJ laboratory strain, naturally recovered in Italy in 2018. The molecule conforms to the typical model of animal mitochondrial genomes. Gene order is identical to that of its congeneric Trissolcus basalis . Phylogenetic analysis confirms its placement within monophyletic Scelionidae and Telenominae as the sister group of T. basalis .